What We Learned about Mentoring Research Assistants Employed in a Complex, Mixed-Methods Health Study - Weeks, Lori E.; Villeneuve, Michelle A.; Hutchinson, Susan; Roger, Kerstin; Versnel, Joan; Packer, Tanya (Canadian Journal of Higher Education, 2015)
We investigated the experiences of research assistants in their dual role as both employees and trainees, when they were employed in a complex, mixedmethods, Canadian study on the everyday experience of living with and managing a chronic condition. A total of 13 research assistants participated in one or more components of this study: a survey (n = 11), focus group interview (n = 7), and/or individual interview (n = 13). Thematic analysis identified two key themes: what faculty mentors should provide to research assistants before they begin their work, and what faculty mentors need to know in order to effectively offer ongoing support to research assistants. Our results provide valuable insights for new and experienced faculty members who employ research assistants and for research assistants employed in funded research projects. Our results can inform the development of regulations to ensure that research assistants have greater protection as both trainees and employees.